The Effect of Eating Attitude Disorder in Adolescents on Subjective WellBeing, Depression, Anxiety and Stress - Demir, Yasin; Kumcağız, Hatice (Şahin ORUÇ, 2020)
The aim of this study is to examine the relationship between eating attitude disorder, subjective well-being, depression, anxiety and stress on adolescents. For this purpose, 482 adolescents have been reached. In the research, "Eating Attitude Test", "Subjective Well-Being Scale" and "Depression, Anxiety and Stress Scale" were used as data collection tools. SPSS and AMOS package programs were used in the analysis of the data. A positive correlation was found between eating attitude disorder and depression, anxiety and stress and it was found that there was a negative relationship between eating attitude disorder and subjective well-being. It was observed that there was a negative relationship between subjective well-being and depression, anxiety and stress. Eating attitude disorders in adolescents affect subjective well-being negatively. Finally, it was concluded that subjective wellbeing negatively affects depression, anxiety and stress. The results are discussed in the literature perspective and suggestions are made.

Bu çalışmanın amacı ergenlerde yeme tutum bozukluğu, öznel iyi oluş, depresyon, anksiyete ve stres arasındaki ilişkilerin incelenmesidir. Bu amaç doğrultusunda 482 ergene ulaşılmıştır. Araştırmada veri toplama araçları olarak “Yeme Tutum Testi”, “Öznel İyi Oluş Ölçeği” ile “Depresyon, Anksiyete ve Stres Ölçeği” kullanılmıştır. Verilerin analizinde SPSS ve AMOS paket programları kullanılmıştır. Yeme tutum bozukluğu ile depresyon, anksiyete ve stres arasında pozitif yönde; öznel iyi oluş arasında ise negatif yönde anlamlı ilişkiler olduğu saptanmıştır.Öznel iyi oluş ile depresyon, anksiyete ve stres arasında ise negatif yönde ilişki olduğu görülmüştür. Ergenlerde yeme tutum bozukluğu, öznel iyi oluşu olumsuz yönde etkilemektedir. Son olarak öznel iyi oluşun depresyon, anksiyete ve stresi olumsuz yönde etkilediği sonucuna ulaşılmıştır. Sonuçlar literatür perspektifinde tartışılmış ve önerilerde bulunulmuştur.
Ergenlerde Yeme Tutum Bozuklukluğunun Öznel İyi Oluş, Depresyon, Anksiyete ve Stres Üzerine Etkisi